The impact of technological innovation and strategic CSR on firm value: Implication for social open innovation - Soohwan Choi; Jaewook Yoo (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study was designed to explore the effects of strategic CSR conformity and technological innovation activities on the market value of Korean manufacturing firms. We proposed a research model based on resource-based, stakeholder, and institutional theories to examine the main effects of technological innovation activities and strategic CSR conformity, as well as their interaction effect on firm value. The findings showed that technological innovation activities have a significant positive impact on the firm value, whereas strategic CSR conformity does not. They also presented that the interaction between technological innovation activities and strategic CSR conformity had a negative effect on firm value, contrary to what was expected in hypothesis 3. Thus, further analysis was performed by dividing the sample into two subgroups: the upper group (above the mean) and the lower group (below the mean). The results showed that the interaction effect between strategic CSR and technological innovation activities had a significant positive impact on the market value of Korean manufacturing firms. This finding implies that a firm should invest in strategic CSR at a level higher than the industry average to intensify the positive effect of technological innovation activities on firm value.
Keywords: 650; conformity; firm value; strategic CSR; technology innovation